River people [videorecording (VHS)] : behind the case of David Sohappy - Conford, Michal; Zaccheo, Michele (Filmakers Library, 1990)
Portrays a traditional community of fishermen at odds with the ways of modernity. Follows the story of David Sohappy, a Native American spiritual leader who was sentenced to a five-year prison term for selling 317 salmon out of season, becoming a symbol of resistance for indigenous people of the Pacific Northwest and beyond. Explores the historic conflict over the resources of the Columbia River and the political controversy involving fishing rights and the right to religious freedom.